Conductive composition for molded film, molded film and its manufacturing method, and molded body and its manufacturing method
Patent Information
- Application Number
- JP2020200672
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-03
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2040-12-03
AI Technical Summary
【0016】 本発明によれば、引張力および高温下応力ストレスによる導電性の低下が抑制された成形フィルムを製造可能な成形フィルム用導電性組成物、引張力および高温下応力ストレスによる導電性の低下が抑制された成形フィルム、及び、導電性に優れた成形体及びその製造方法を提供することができる。
Smart Images

Figure 0007631765000004 
Figure 0007631765000005 
Figure 0007631765000006
Abstract
Description
[Technical field]
[0001] The present invention relates to a conductive composition for a molded film, a molded film and a method for producing the same, and a molded article and a method for producing the same. [Background technology]
[0002] Patent Document 1 discloses a specific conductive circuit integrated molded product having a resin molded body, a base film embedded flush with one side of the resin molded body, and a conductive circuit disposed between the resin molded body and the base film. Patent Document 1 describes a method for manufacturing the conductive circuit-integrated molded product, in which a base film on which a specific conductive circuit is formed is placed on the cavity surface of an injection molding die, and then molten resin is injected to injection mold a resin molded body. In Patent Document 1, the conductive circuit is formed by etching a specific transparent thin metal film.
[0003] A printing method using conductive ink has been considered as a method for forming a conductive circuit to replace the etching method. The method of printing conductive ink does not require any complicated steps compared to the etching method, and can easily form a conductive circuit, improving productivity and reducing costs. For example, Patent Document 2 discloses a specific conductive ink containing specific conductive fine particles and a specific epoxy resin as a low-temperature processing type conductive ink capable of forming a high-definition conductive pattern by screen printing. It is said that the screen printing makes it possible to form a thick conductive pattern, and thus realizes low resistance of the conductive pattern.
[0004] Furthermore, Patent Document 3 discloses a method for manufacturing a decorative sheet capable of expressing a three-dimensional effect, in which a laminate having a printed layer printed in a pattern on a transparent resin layer and a laminate sheet having a decorative layer on a base film are thermocompression-bonded to each other, thereby giving the decorative layer an uneven shape that follows the pattern of the printed layer. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2012-11691 A [Patent Document 2] JP 2011-252140 A [Patent Document 3] JP 2007-296848 A Summary of the Invention [Problem to be solved by the invention]
[0006] According to the method of Patent Document 1, a conductor can be easily provided on the surface of a molded body. On the other hand, there is an increasing demand for forming a conductive circuit on the surface of a substrate having various shapes, such as a substrate having an uneven surface or a curved surface. When a conductive circuit is formed by laminating a film having a conductive layer on the surface of such a substrate, the film needs to be deformed to match the surface shape of the substrate. When the film is deformed, a large tensile force may be generated partially in the conductive layer. The tensile force causes breakage of the conductive layer, and a decrease in conductivity becomes a problem. Furthermore, when forming a conductive circuit on a substrate having such an uneven surface or a curved surface, it is necessary to integrate the film and the substrate after or at the same time as deforming the film having the conductive layer, and in this integration process, stress is applied to the conductive circuit due to friction with the plastic substrate at high temperature. The stress at high temperature also causes breakage of the conductive layer, and a decrease in conductivity becomes a problem.
[0007] The present invention has been made in consideration of the above-mentioned circumstances, and has an object to provide a conductive composition for a molded film capable of producing a molded film in which the decrease in conductivity due to tensile force and high-temperature stress is suppressed, a molded film in which the decrease in conductivity due to tensile force and high-temperature stress is suppressed, and a molded body with excellent conductivity and a method for producing the same. [Means for solving the problem]
[0008] The conductive composition for a molded film according to the present embodiment is a conductive resin composition for producing a molded film for forming a conductive circuit on a substrate surface having an uneven surface or a three-dimensional curved surface, A conductive resin composition for molded films comprising (A) a resin, (B) a solvent, and (C) conductive fine particles, wherein when a storage modulus is measured in an environment of 25°C while applying a shear (rotation in one direction) speed of 1000 ( / s) for 60 seconds and then a frequency of 1 Hz and a strain of 1% to the sample, the storage modulus at the end of the measurement (200 seconds after the start of the measurement) is taken as 100%, and tan δ at the time when the storage modulus reaches 90% is 0.50 or more and 30 or less.
[0009] One embodiment of the conductive composition for molded films of the present invention has a viscosity at 25° C. and a shear rate of 100 (1 / s) of 3.00 (Pa·s) or more and 300 (Pa·s) or less.
[0010] In one embodiment of the conductive composition for molded films of this embodiment, the resin (A) has at least one reactive functional group selected from the group consisting of a hydroxyl group and a carboxyl group, has a glass transition point of 10°C or higher and 110°C or lower, and has a weight average molecular weight of 10,000 or higher and 100,000 or lower.
[0011] In one embodiment of the conductive composition for molded films of this embodiment, the conductive fine particles (C) have an average particle size of 0.5 μm or more and less than 30 μm, and include at least one type selected from the group consisting of silver powder, copper powder, silver-coated powder, copper alloy powder, and carbon fine particles.
[0012] In one embodiment of the conductive composition for a molded film of the present invention, the conductive fine particles (C) contain a flaky conductive powder having an average particle size of 2 μm or more and less than 15 μm.
[0013] The first method for producing a molded body according to the present embodiment includes a step of placing the molded film according to the present embodiment; and b) integrating the molded film and the substrate by an overlay molding process.
[0014] A second method for producing a molded article according to the present embodiment includes forming the molded film according to the present embodiment into a predetermined shape, placing the formed film in an injection mold; and forming a substrate by injection molding and integrating the formed film with the substrate.
[0015] A third manufacturing method of the molded body according to the present embodiment includes the steps of placing the molded film according to the present embodiment in an injection molding mold, and molding a substrate by injection molding and transferring the conductive layer in the molded film to the substrate. Effect of the Invention
[0016] According to the present invention, it is possible to provide a conductive composition for a molded film capable of producing a molded film in which the decrease in conductivity due to tensile force and high-temperature stress is suppressed, a molded film in which the decrease in conductivity due to tensile force and high-temperature stress is suppressed, and a molded body with excellent conductivity and a method for producing the same. [Brief description of the drawings]
[0017] [Figure 1] FIG. 2 is a schematic cross-sectional view showing an example of a molded film according to the present embodiment. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing another example of the molded film of the present embodiment. [Diagram 3] FIG. 2 is a schematic process diagram showing an example of a first manufacturing method of a molded body. [Figure 4] FIG. 4 is a schematic process diagram showing another example of the second manufacturing method of a molded body. [Diagram 5] 5A to 5C are schematic process diagrams showing another example of the third manufacturing method of a molded body. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] The conductive composition for a molded film, the molded film, the molded article, and the method for producing the same according to the present embodiment will be described in detail below. In the present embodiment, the term "cured product" refers not only to products that have been cured by chemical reaction, but also to products that have been cured without chemical reaction, such as products that have been hardened by evaporation of a solvent.
[0019] [Conductive composition for molded films] The conductive composition for a molded film of the present invention is a conductive resin composition for producing a molded film for forming a conductive circuit on a substrate surface having an uneven surface or a three-dimensional curved surface, A conductive resin composition for molded films comprising (A) a resin, (B) a solvent, and (C) conductive fine particles, characterized in that when a storage modulus is measured while applying a shear (rotation in one direction) speed of 1000 ( / s) for 60 seconds in an environment of 25°C and then a frequency of 1 Hz and a strain of 1% to the sample, the value at the end of the storage modulus measurement (200 seconds after the start of the measurement) is taken as 100%, and the tan δ at the time when the storage modulus reaches 90% is 0.50 or more and 30 or less.
[0020] The present inventors have studied a screen-printable conductive composition in order to produce a molded film that is applicable to a non-flat substrate surface and has process suitability for the integration process with a plastic substrate. In order to apply the composition to the production of a molded film, the rheological properties, resin structure, conductive fine particles, and solvent were adjusted and studied in various ways, and it was found that by setting the rheological properties of the conductive resin composition within a specific range, the frequency of cracks occurring when the obtained molded film is tensilely deformed at a moldable high temperature is different. As a result of the study conducted by the present inventors based on such knowledge, it has become clear that when a conductive resin composition that does not satisfy the above-mentioned rheological property range is printed and heated and dried, significant conductivity deterioration of the conductive layer pattern and cracks in the conductive layer occur when the molded film is deformed by tension at a high temperature corresponding to its softening point. The same was true when a conductive layer is provided on a decorative layer.
[0021] Even if the molded film has a conductive layer that cracks or a large change in resistance value occurs when deformed by pulling at such high temperatures, there is no problem when it is used alone as a flat film circuit board or when it is used in a bent state on a two-dimensional curved surface. However, when it is used as a molded film that is integrated with the shape of a non-flat substrate surface, such as an uneven shape or a three-dimensional curved shape, the molded film will be deformed. Therefore, it is predicted that the conductive layer cannot follow the deformation of the resin film and peels off or breaks from the base film, resulting in a decrease in the conductivity of the conductive layer. In addition, the uneven surface and three-dimensional curved surface in the present invention refer not only to a surface having a gently curved cross section, but also to a three-dimensional surface having an acute angle or a rectangular shape in general. In other words, it refers to a three-dimensional shape that cannot be established only by deforming a plane without expanding or contracting, such as a hemispherical, conical, cylindrical, or rectangular prism. In addition, when a certain three-dimensional shape has elements of both the above-mentioned plane or two-dimensional curved surface and a three-dimensional curved surface in a continuous three-dimensional surface, for example, a three-dimensional shape in which one or more partial hemispherical shapes are combined with a plane shape, it is a three-dimensional shape that cannot be established by deforming a plane as a whole without expanding or contracting, and is also considered to be a three-dimensional curved surface. In other words, the uneven surface and three-dimensional curved surface in the present invention cannot be realized by bending a flexible substrate or the like, and are shapes that can be realized, for example, by forming a moldable film by three-dimensional molding under heating.
[0022] The inventors conducted intensive research based on these findings, and as a result, they found that when a conductive resin composition is subjected to a shear (rotation in one direction) speed of 1000 ( / s) for 60 seconds in an environment of 25°C, and then the storage modulus is measured while applying a strain of 1 Hz frequency to the sample, the storage modulus value at the end of the storage modulus measurement (200 seconds after the start of the measurement) is taken as 100%, and when the storage modulus reaches a value of 90%, the change in resistance value that occurs when the molded film is pulled with a particularly large degree of deformation is small when tan δ is 0.5 or more and 30 or less, and they have completed the present invention. That is, by satisfying the above conditions, the conductive composition for molded films of the present invention can easily produce a molded film having a thick conductive layer with excellent conductivity by screen printing or the like. In addition, a molded film produced using the conductive composition for molded films can suppress a decrease in conductivity even when used on a non-flat substrate surface. Furthermore, by using the molded film, a molded product can be obtained in which a conductive circuit is formed on any surface, such as an uneven surface or a curved surface, on a substrate made of a three-dimensional plastic having practical strength.
[0023] The conductive composition for molded films of the present embodiment contains at least a resin (A), a solvent (B), and conductive fine particles (C), and may further contain other components as necessary. Each component of such a conductive composition for molded films will be described below.
[0024] <Resin (A)> The conductive composition of the present embodiment contains a binder resin (A) to provide film-forming properties and adhesion to the base film or decorative layer. In addition, in the present embodiment, the resin (A) can provide flexibility to the conductive layer. Therefore, the resin (A) can be contained to suppress breakage of the conductive layer due to stretching.
[0025] The resin (A) can be appropriately selected from resins used in conductive compositions. Examples of the resin (A) include acrylic resins, vinyl ether resins, polyether resins, polyester resins, polyurethane resins, epoxy resins, phenoxy resins, polycarbonate resins, polyvinyl chloride resins, polyolefin resins, styrene block copolymer resins, polyamide resins, and polyimide resins. These may be used alone or in combination of two or more.
[0026] Here, the method for measuring the glass transition point is defined. In this specification, the glass transition point was determined by DSC (Differential Scanning Calorimetry). For the optional component whose glass transition point is to be determined, a first heating run, then a cooling run, and then a second heating run are measured. The heating rate in the first heating run and the second heating run is 10°C / min, and the cooling rate in the cooling run is also 10°C / min. In the DSC diagram, a step is obtained in the glass transition region of the optional component during the second heating run. The glass transition temperature of the optional component corresponds to the temperature at a point half the height of the step in the DSC diagram.
[0027] The glass transition point of the resin (A) is from 10°C to 110°C, more preferably from 15°C to 105°C, and even more preferably from 30°C to 100°C, from the viewpoint of maintaining electrical conductivity during stretching in molding and resistance to frictional stress with the substrate plastic at high temperatures in the integration step with the plastic substrate. By being in the above range, an increase in the resistance value of the conductive layer pattern due to stretching of the molded film during molding can be suppressed. From the same viewpoint, when the resin (A) has multiple glass transition points, it is preferable that none of the glass transition points is less than 0°C.
[0028] Furthermore, the weight average molecular weight of the resin (A) is from 10,000 to 100,000, more preferably from 15,000 to 90,000, and even more preferably from 20,000 to 85,000. By making the weight average molecular weight 10,000 or more, improved stretchability due to intermolecular interactions can be expected, and by making it 100,000 or less, good screen printing suitability can be exhibited, which is preferable.
[0029] In this embodiment, the resin (A) may be synthesized by the methods described in the Examples below or other known methods, or a commercially available product having the desired physical properties may be used. In this embodiment, the resin (A) may be used alone or in combination of two or more kinds.
[0030] The content of the resin (A) in the conductive composition of this embodiment is not particularly limited and may be appropriately adjusted according to the application, etc., but is preferably 5% by mass or more and 50% by mass or less, and more preferably 8% by mass or more and 40% by mass or less, based on the total solid content contained in the conductive composition. If the content of the resin (A) is equal to or more than the above lower limit, the film-forming property and the adhesion to the base film, etc. are improved, and flexibility can be imparted to the conductive layer. If the content of the resin (A) is equal to or less than the above upper limit, the content of the conductive fine particles (C) can be relatively increased, and a conductive layer with excellent conductivity can be formed.
[0031] <Solvent (B)> In this embodiment, a solvent (B) is contained in order to dissolve the resin (A) and impart fluidity to impart printability, and to adjust the spread and entanglement of molecular chains in the composition of the resin (A). In addition, in this embodiment, the solvent (B) is contained, and the spread of the molecular chains is adjusted, and wettability is imparted to the base film during printing, thereby improving the patterning accuracy during printing.
[0032] The solvent (B) is not particularly limited, but from the viewpoint of continuous screen printing, it is preferable that the boiling point is 180° C. or more and 270° C. or less. Examples of the solvent include, but are not limited to, diethylene glycol monoethyl ether acetate, gamma butyrolactone, isophorone, tetralin, and dipropylene glycol monomethyl ether acetate.
[0033] <Conductive fine particles (C)> The conductive fine particles (C) exhibit conductivity when multiple conductive fine particles come into contact with each other within the conductive layer, and in this embodiment, an appropriate conductive fine particle is selected from those that can obtain conductivity without being heated at high temperatures. The conductive fine particles used in this embodiment include metal fine particles, carbon fine particles, conductive oxide fine particles, and the like. Examples of metal fine particles include powders of metal elements such as gold, silver, copper, nickel, chromium, palladium, rhodium, ruthenium, indium, aluminum, tungsten, malbutene, and platinum, as well as alloy powders such as copper-nickel alloys, silver-palladium alloys, copper-tin alloys, silver-copper alloys, and copper-manganese alloys, and metal-coated powders in which the surfaces of the above-mentioned metal element powders or alloy powders are coated with silver or the like. Examples of carbon fine particles include carbon black, graphite, and carbon nanotubes. Examples of conductive oxide fine particles include silver oxide, indium oxide, tin oxide, zinc oxide, and ruthenium oxide.
[0034] In this embodiment, it is preferable to contain one or more conductive fine particles selected from silver powder, copper powder, silver-coated powder, copper alloy powder, conductive oxide powder, and carbon fine particles. By using these conductive fine particles (C), a conductive layer with excellent conductivity can be formed without sintering, and a conductive layer with excellent extensibility and conductivity retention performance when molded into a three-dimensional shape as a molded film described later can be formed.
[0035] The shape of the conductive fine particles (C) is not particularly limited, and spherical, flake-like, chain-aggregated, and other shapes can be used as appropriate. From the viewpoints of maintaining printability and maintaining conductivity during molding and stretching, flake-like or chain-aggregated shapes are particularly preferred. In the present invention, "spherical" refers to particles in general that are spherical, oval, crushed spherical, pebble-like, or polyhedral and have a low aspect ratio, specifically, particles with an aspect ratio of about 1 or more and 2 or less. In addition, in the present invention, "flake-like" refers to two-dimensional flat shapes generally called scale-like, plate-like, flat, sheet-like, etc., and among these, those with an aspect ratio of 3 or more and 500 or less are particularly preferred. In addition, in the present invention, "chain-aggregated" refers to amorphous shapes generally in which a plurality of the above-mentioned spherical conductive fine particles are directly fused or bonded together.
[0036] The D50 particle size of the conductive fine particles (C) is not particularly limited, but from the viewpoint of maintaining dispersibility and printability in the conductive composition, maintaining conductivity during molding, and resistance to injection molding process with molten resin or high temperature friction resistance of molded resin, it is preferably 0.2 μm or more and less than 30 μm, and particularly preferably 0.7 μm or more and less than 15 μm. In this embodiment, the average particle size of the conductive fine particles (C) is calculated as follows. In accordance with the laser diffraction and scattering method described in JIS M8511 (2014), a laser diffraction and scattering type particle size distribution measuring device (Microtrack 9220FRA manufactured by Nikkiso Co., Ltd.) is used to add an appropriate amount of conductive fine particles (C) to an aqueous solution containing 0.5 vol% of a commercially available surfactant polyoxyethylene octylphenyl ether (Triton X-100 manufactured by Roche Diagnostics Co., Ltd.) as a dispersant, and then irradiated with 40 W ultrasonic waves for 180 seconds while stirring, and then measurement was performed. The calculated median diameter (D50) value was taken as the average particle size of the conductive fine particles (C).
[0037] In the present embodiment, the conductive fine particles (C) may be used alone or in combination of two or more kinds. The content of the conductive fine particles (C) in the conductive composition of this embodiment is not particularly limited and may be appropriately adjusted according to the application, etc., but is preferably 50% by mass or more and 90% by mass or less, and more preferably 55% by mass or more and 85% by mass or less, based on the total solid content contained in the conductive composition. If the content of the conductive fine particles (C) is equal to or more than the above lower limit, a conductive layer with excellent conductivity can be formed. In addition, if the content of the conductive fine particles (C) is equal to or less than the above upper limit, the content of the resin (A) can be increased, improving film-forming properties and adhesion to a base film, etc., and imparting flexibility to the conductive layer.
[0038] <Optional ingredients> The conductive composition of the present invention may further contain other components as necessary, such as a crosslinking agent, a dispersant, an anti-friction improver, an infrared absorbing agent, an ultraviolet absorbing agent, an aromatic, an antioxidant, an organic pigment, an inorganic pigment, an antifoaming agent, a silane coupling agent, a plasticizer, a flame retardant, a moisturizing agent, etc.
[0039] <Method of manufacturing conductive composition> The method for producing the conductive composition of this embodiment may be any method for dissolving or dispersing the resin (A), the solvent (B), the conductive fine particles (C), and other components used as necessary, and the conductive composition can be produced by mixing them by a known mixing means.
[0040] [Formed film] The molded film of this embodiment is a molded film having a conductive layer on a base film, The conductive layer is a cured product of the conductive composition for molded films. According to the molded film of this embodiment, a molded article can be obtained in which a conductive circuit is formed on any substrate surface, such as an uneven surface or a curved surface. According to the molded film of this embodiment, a molded article can be obtained in which a conductive circuit is formed on any substrate surface, such as an uneven surface or a curved surface. The layer structure of the molded film of this embodiment will be described with reference to Figures 1 and 2. Figures 1 and 2 are schematic cross-sectional views showing an example of the molded film of this embodiment. The molded film 10 shown in the example of Fig. 1 has a conductive layer 2 on a base film 1. The conductive layer 2 may be formed on the entire surface of the base film 1, or may be formed in a desired pattern as in the example of Fig. 1. The molded film 10 shown in the example of Fig. 2 has a decorative layer 3 on a base film 1, and a conductive layer 2 on the decorative layer 3. As shown in the example of Fig. 2, the molded film 10 may also have, on the conductive layer 2, an electronic component 4 and a pin 5 for connecting to an output circuit. Although not shown, a resin layer for protecting the conductive layer or the electronic component 4 may be provided on the conductive layer 2 or the electronic component 4, and the resin layer may serve as an adhesive layer or bonding layer for improving adhesion to the substrate described below. In addition, although not shown in the figure, when the molded film 10 of this embodiment has a decorative layer 3, in addition to the example of Figure 2, it may have a layer structure having a decorative layer 3 on one side of the base film 1 and a conductive layer 2 on the other side. The molded film of the present embodiment comprises at least a base film and a conductive layer, and may have other layers as required. Each layer of such a molded film will be described below.
[0041] <Base film> In this embodiment, the base film can be appropriately selected from those having flexibility and extensibility to such an extent that it can follow the shape of the substrate surface under the molding temperature conditions when the substrate is formed, and it is preferable to select the base film according to the use of the molded body and the manufacturing method of the molded body. For example, when the overlay molding method or the film insert method described below is adopted as a method for producing a molded body, the base film remains in the molded body, so the base film can be selected taking into consideration its function as a protective layer for the conductive layer. On the other hand, when an in-mold transfer method, which will be described later, is employed as a method for producing a molded article, it is preferable to select a base film having releasability.
[0042] The base film can be appropriately selected from the above viewpoints, and may be, for example, a film such as polycarbonate, polymethyl methacrylate, polyethylene terephthalate, polystyrene, polyimide, polyamide, polyethersulfone, polyethylene naphthalate, polybutylene terephthalate, polyvinyl chloride, polyethylene, polypropylene, cycloolefin polymer, ABS (acrylonitrile-butadiene-styrene copolymer resin), AES (acrylonitrile-ethylene-styrene copolymer resin), Kaidac (acrylic modified vinyl chloride resin), modified polyphenylene ether, and a polymer alloy consisting of two or more of these resins, or a laminated film thereof. Among them, a film selected from polycarbonate, polymethyl methacrylate, polypropylene, and polyethylene terephthalate, or a laminated film thereof is preferable. As the laminated film, a laminated film of polycarbonate and polymethyl methacrylate is preferable. The method for producing the laminated film of polycarbonate and polymethyl methacrylate is not particularly limited. A polycarbonate film and a polymethyl methacrylate film may be laminated together, or polycarbonate and polymethyl methacrylate may be co-extruded to form a laminated film. It is also preferable that the surface of these base films is subjected to a modification treatment such as a corona treatment.
[0043] In addition, if necessary, an anchor coat layer may be provided on the base film and the conductive composition may be printed on the anchor coat layer for the purpose of improving the printability of the conductive composition. The anchor coat layer is not particularly limited as long as it has good adhesion to the base film and further to the conductive composition and follows the film during molding, and organic fillers such as resin beads and inorganic fillers such as metal oxides may also be added as necessary. The method of providing the anchor coat layer is not particularly limited, and it can be obtained by coating, drying, and curing using a conventionally known coating method. Furthermore, if necessary, in order to prevent the surface of the molded body from being scratched, a hard coat layer may be provided on the base film, and a conductive composition and, if necessary, a decorative layer may be printed on the opposite side. The hard coat layer is not particularly limited as long as it has good adhesion to the base film and surface hardness and follows the film during molding, and organic fillers such as resin beads and inorganic fillers such as metal oxides may also be added as necessary. The method for providing the hard coat layer is not particularly limited, and it can be obtained by applying, drying, and curing using a conventionally known coating method.
[0044] When the molded film of this embodiment has a decorative layer, it is preferable to select a base film having transparency.
[0045] The thickness of the base film is not particularly limited, but can be, for example, from 10 μm to 500 μm, and preferably from 20 μm to 450 μm.
[0046] <Conductive layer> In the molded film of this embodiment, the conductive layer is a cured product of the conductive composition. The conductive layer may be a patterned conductive layer or a solid conductive layer. The method for forming the conductive layer is not particularly limited, but in this embodiment, it is preferable to form it by screen printing, pad printing, stencil printing, screen offset printing, dispenser printing, gravure offset printing, reverse offset printing, or microcontact printing, and it is more preferable to form it by screen printing. In the screen printing method, it is preferable to use a fine mesh screen, particularly a fine mesh screen of about 300 to 650 mesh, in order to meet the demands of high-definition conductive circuit patterns. In this case, the open area of the screen is preferably about 20 to 50%. The screen wire diameter is preferably about 10 to 70 μm. Types of screens include polyester screens, combination screens, metal screens, nylon screens, etc. When printing with a highly viscous paste, a high-tension stainless steel screen can be used. The squeegee for screen printing may be round, rectangular, or square, and an abrasive squeegee may be used to reduce the attack angle (the angle between the plate and the squeegee during printing). Other printing conditions may be appropriately designed from conventionally known conditions.
[0047] The conductive composition is printed by screen printing, and then heated to dry and cause a crosslinking reaction and harden. For sufficient volatilization of the solvent and crosslinking reaction, the heating temperature is preferably 80 to 230° C. and the heating time is preferably 10 to 120 minutes, thereby making it possible to obtain a patterned conductive layer. The pattern of the conductive layer is not particularly limited, and may be, for example, a straight line, a curve, a mesh, a solid pattern or a solid pattern having a partial square, circle, diamond shape, or any combination thereof, or the entire conductive layer may be a solid pattern on one side, and is not limited as long as the conductive layer functions as a conductive circuit or as a part of a conductive circuit. The patterned conductive layer may be provided with an insulating layer, if necessary, so as to cover the conductive pattern. The insulating layer is not particularly limited, and any known insulating layer may be used.
[0048] The thickness of the conductive layer may be appropriately adjusted depending on the required conductivity, etc., and is not particularly limited. For example, it can be 0.5 μm or more and 20 μm or less, and preferably 1 μm or more and 15 μm or less.
[0049] <Decorative layer> The molded film of the present embodiment may have a decorative layer from the viewpoint of the design of the resulting molded article. The decorative layer may be a layer having a single color, or may have any pattern. For example, the decorative layer can be formed by preparing a decorative ink containing a coloring material, a resin, and a solvent, and then applying the decorative ink to the base film by a known printing method. The coloring material can be appropriately selected from known pigments and dyes, and the resin is preferably appropriately selected from the same resins as the resin (A) in the conductive composition of the present embodiment. The thickness of the decorative layer is not particularly limited, but may be, for example, from 0.5 μm to 10 μm, and preferably from 1 μm to 5 μm.
[0050] [Molded body] The molded article of this embodiment is a molded article having at least a conductive layer laminated on a substrate, and the conductive layer is a cured product of the conductive composition for molded films according to any one of claims 1 to 5. The molded article of this embodiment is formed from a molded film using the conductive composition for molded films of this embodiment, and therefore is a molded article having a conductive circuit formed on any surface, such as an uneven surface or a curved surface. Hereinafter, three embodiments of the method for producing the molded body of the present embodiment will be described. Note that the molded body of the present embodiment may be produced by using the conductive composition of the present embodiment, and the method is not limited to these embodiments.
[0051] <First manufacturing method> A first method for producing a molded body according to the present embodiment includes the steps of: printing the conductive composition for a molded film according to the present embodiment on a base film and drying the composition to produce a molded film; placing the formed film on a substrate; and b) integrating the molded film and the substrate by an overlay molding process. The following description will be given with reference to FIG. 3, but as the method for producing the molded film is as described above, the description will be omitted here.
[0052] Fig. 3 is a schematic process diagram showing an example of a first manufacturing method of a molded body. Fig. 3(A) to (C) each illustrate a molded film 10 and a substrate 20 arranged in a chamber box of a TOM (Three dimension Overlay Method) molding machine, while Fig. 3(B) and (C) omit the chamber box. In the first manufacturing method, first, the substrate 20 is placed on the table of the lower chamber box 22. Next, the molded film 10 of the present embodiment is passed between the upper chamber box 21 and the lower chamber box 22 and placed on the substrate 20. At this time, the molded film 10 may be placed so that the conductive layer faces either the substrate 20 side or the opposite side to the substrate 20, and this is selected depending on the final use of the molded body. Next, the upper and lower chamber boxes are placed in a vacuum state, and the molded film is heated. Next, the table is raised to raise the substrate 20 15. Next, only the inside of the upper chamber box 21 is opened to the atmosphere (FIG. 3(B)). At this time, the molded film is pressed against the substrate side 16, and the molded film 10 and the substrate 20 are bonded together and integrated (FIG. 3(C)). In this manner, a molded body 30 can be obtained.
[0053] In the first manufacturing method, the base material 20 can be prepared in advance by any method. In the first manufacturing method, the material of the base material 20 is not particularly limited, and the base material 20 may be made of resin or metal.
[0054] In this first manufacturing method, the frictional stress with the substrate plastic at high temperatures in the above-mentioned integration step with the substrate is caused by the frictional stress between the conductive circuit of the molded film and the substrate at high temperatures when the molded film in Fig. 3(C) is pressed 16 toward the substrate and the molded film 10 and substrate 20 are bonded together to be integrated. That is, in this first manufacturing method, the conductive layer is simultaneously subjected to a load due to tensile stress during molding and frictional stress with the substrate plastic at high temperatures.
[0055] <Second manufacturing method> A second method for producing a molded body according to the present embodiment includes the steps of: printing the conductive composition for molded film according to the present embodiment on a base film and drying the composition to produce a molded film; forming the formed film into a predetermined shape; placing the formed film in an injection mold; and forming a substrate by injection molding and integrating the formed film with the substrate. Hereinafter, the method will be described with reference to Fig. 4. The second manufacturing method is sometimes called a film insert method.
[0056] FIG. 4 is a schematic process diagram showing an example of the second manufacturing method of the molded body. In the second manufacturing method, the molded film 10 is molded into a predetermined shape in advance by a mold 11 (FIG. 4(A)). After or while being softened by heating, the molded film 10 is suctioned into the mold by vacuum or pressed against the mold by compressed air, or both, and molded by the mold 11 (FIG. 4(B)). At this time, the molded film 10 may be molded so that the conductive layer faces either the substrate 20 side described later or the opposite side to the substrate 20, and this is selected depending on the final use of the molded body. Next, the molded molded film 10 is placed in a mold 12 for injection molding (FIGS. 4(C) to 4(D)). Next, resin is injected 14 from an opening 13 to form the substrate 20, and the molded film 10 and the substrate 20 are integrated to obtain a molded body 30 (FIG. 4(E)).
[0057] In the second manufacturing method, it is not necessary to prepare the substrate 20 in advance, and the molding of the substrate and the integration with the molded film can be performed simultaneously. The material of the substrate 20 can be appropriately selected from known resins used for injection molding.
[0058] In this second manufacturing method, the frictional stress with the base plastic at high temperatures in the above-mentioned integration step with the substrate is caused by the frictional stress that the conductive layer on the molded film receives when high-temperature molten resin is injected into a mold when resin is injected 14 from opening 13 in Fig. 4(E) to form substrate 20 and the molded film 10 and substrate 20 are integrated. That is, in this second manufacturing method, the conductive layer is subjected to a load due to tensile stress during molding, and then is subjected to frictional stress with the base plastic at high temperatures in a separate step.
[0059] <Third manufacturing method> The third method for producing a molded body according to the present embodiment includes the steps of: printing the conductive composition for molded film according to the present embodiment on a base film by screen printing; and drying the composition to produce a molded film. placing the formed film in an injection mold; The method includes a step of molding a substrate by injection molding and transferring the conductive layer in the molded film to the substrate side. Hereinafter, the method will be described with reference to Fig. 5. The third manufacturing method is sometimes called an in-mold transfer method.
[0060] FIG. 5 is a schematic process diagram showing an example of the third manufacturing method of the molded body. In the third manufacturing method, the molded film 10 is selected and used as a base film having releasability. The molded film 10 is placed in a mold 12 for injection molding so that the conductive layer faces the substrate 20 side described later (FIG. 5(A)). Next, resin is injected 14 from an opening 13 to form the substrate 20, and the molded film 10 and the substrate 20 are adhered to each other, and at least the conductive layer is transferred to the substrate 20 side (FIG. 5(B)), and the molded body 30 is obtained (FIG. 5(C)). In addition, when the molded film 10 has a decorative layer, the decorative layer and the conductive layer are transferred.
[0061] In the third manufacturing method, since it is not necessary to cut the base film, a long base film can be arranged as shown in the example of Fig. 5. The material of the substrate 20 can be appropriately selected from known resins used for injection molding.
[0062] In this third manufacturing method, the frictional stress with the base plastic at high temperatures in the above-mentioned integration step with the base material is caused by the frictional stress that the conductive layer on the molded film receives when high-temperature molten resin is injected into the mold when resin is injected 14 from the opening 13 in Fig. 5(C) to form the base material 20 and the molded film 10 and the base material 20 are adhered to each other. That is, in this third manufacturing method, the conductive layer is simultaneously subjected to a load due to tensile stress during molding and frictional stress with the base plastic at high temperatures.
[0063] The molded articles obtained in this way make it possible to mount circuits, touch sensors and various electronic components on the plastic housings of home appliances, automobile parts, robots, drones, etc. They are also extremely useful for making electronic devices lighter, thinner, shorter and smaller, improving design freedom and increasing functionality. EXAMPLES
[0064] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In the examples, "parts" means "parts by mass" and "%" means "% by mass". The weight average molecular weight in the examples is a polystyrene-equivalent molecular weight measured using a GPC (gel permeation chromatography) "HLC-8320" manufactured by Tosoh Corporation.
[0065] In addition, a specific method for measuring tan δ when the storage modulus in the examples is restored to 90% will be described. Using a rheometer MCR-302 manufactured by Anton Paar, a cone plate of 25 mm and a measurement temperature of 25° C., a shear of 1000 (1 / s) was applied for 60 seconds, and then the shear was stopped, and the storage modulus and loss modulus were measured for 200 seconds under a frequency of 1 Hz and a strain of 1%. The tan δ at the point where the storage modulus value at the end of the measurement has reached 90% of its value is defined as the “recovery tan δ”.
[0066] The viscosity in the examples was measured using the same equipment and temperature conditions as above, while continuously changing the shear rate from 1 (1 / s) to 100 (1 / s), and the viscosity at 100 (1 / s) is defined as "high shear viscosity." The condition for increasing the shear rate was a program that required 60.5 seconds to increase the shear rate from 1 (1 / s) to 10 (1 / s), and 10.5 seconds to increase the shear rate from 10 (1 / s) to 100 (1 / s).
[0067] <Resins (A-1) to (A-11)> The following resins were used as resins (A-1) to (A-11). Resin (A-1): Acrylic resin manufactured by Mitsubishi Chemical Corporation, Dianale BR85, glass transition point 105°C, weight average molecular weight 32,0000. Does not contain either hydroxyl or carboxyl groups as reactive functional groups. Resin (A-2): Polyester resin manufactured by Unitika, Elitel UE-3510, glass transition point -25°C, weight average molecular weight 34,000. Contains both hydroxyl and carboxyl groups as reactive functional groups. Resin (A-3): Phenoxy resin manufactured by Mitsubishi Chemical Corporation, JER1256, glass transition point 95°C, weight average molecular weight 50,000. Contains hydroxyl group as reactive functional group. Resin (A-4): Acrylic resin manufactured by Negami Chemical Industries, MAP-4050, glass transition point 31°C, weight average molecular weight 10,000. Contains carboxyl group as reactive functional group.
[0068] Synthesis Example 1: Preparation of Resin (A-5) A reaction apparatus equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen gas inlet tube was charged with 200.0 parts of a polyester polyol obtained from isophthalic acid and 3-methyl-1,5-pentanediol (Kuraray Co., Ltd.'s "Kuraray Polyol P-2030"), 19.0 parts of isophorone diisocyanate, 146.0 parts of butyl carbitol acetate as a solvent, and 0.04 parts of dibutyltin dilaurate as a catalyst, and reacted at 90°C for 3 hours under a nitrogen stream to obtain a urethane resin solution with a non-volatile content of 40% consisting of 40% urethane resin with a weight average molecular weight of 34,000, a glass transition point of 4°C, and a hydroxyl value of 7.3 KOHmg / g and 60% butyl carbitol acetate solvent.
[0069] Resin (A-6): Butyral resin manufactured by Kuraray, Mowital B30T, glass transition point 70 degrees, weight average molecular weight 55,000, contains hydroxyl group as reactive functional group. Resin (A-7): Polyester resin manufactured by Unitika, Elitel UE-3210, glass transition point 45°C, weight average molecular weight 20,000, contains hydroxyl and carboxyl groups as reactive functional groups. Resin (A-8): Nagase ChemteX acrylic resin, SG-P3, MEK solution with 15% solids, glass transition point 12°C, weight average molecular weight 85,000, does not contain any hydroxyl or carboxyl groups as reactive functional groups. Resin (A-9): Nagase ChemteX acrylic resin, SC-280 BCA13, butylcarbaacetate solution with a solid content of 13%, glass transition point -29°C, weight average molecular weight 900,000, containing a carboxyl group as a reactive functional group. Resin (A-10): Phenoxy resin manufactured by Nippon Steel & Sumitomo Metal Chemical Co., Ltd., YP-50S, glass transition point 84°C, weight average molecular weight 60,000, contains hydroxyl group as reactive functional group. Resin (A-11): Polyester resin manufactured by Unitika, XA0847, glass transition point 61°C, weight average molecular weight 8000, contains carboxyl group as reactive functional group.
[0070] The following solvents, conductive fine particles and other components were used. <Solvents (B-1) to (B-5)> Solvent (B-1): Butyl carbitol acetate, boiling point 247℃ Solvent (B-2): ε-caprolactone, boiling point 241℃ Solvent (B-3): Terpineol, boiling point 219℃ Solvent (B-4): Dipropylene glycol methyl ether, boiling point 75°C Solvent (B-5): Methyl ethyl ketone, boiling point 80℃
[0071] <Conductive fine particles (C-1)~(C-9)> Conductive fine particles (C-1): Manufactured by Fukuda Metal Foil & Powder Co., Ltd., flake silver powder, average particle size 5.2 μm ·Conductive fine particles (C-2): Manufactured by Fukuda Metal Foil and Powder Co., Ltd., chain agglomerated silver powder, average particle size 1.5 μm Conductive fine particles (C-3): DOWA Electronics, flake-shaped silver-coated copper powder, silver coating amount 10%, average particle size 4.0 μm Conductive fine particles (C-4): Ito Graphite Co., Ltd., flake graphite, average particle size 15 μm Conductive fine particles (C-5): DOWA Electronics, spherical silver powder, average particle size 3.3 μm Conductive fine particles (C-6): Fukuda Metals Co., Ltd., spherical silver powder, average particle size 0.98 μm Conductive fine particles (C-7): Manufactured by Fukuda Metals, flake silver powder, average particle size 2.76 μm Conductive fine particles (C-8): Fukuda Metals, amorphous silver powder, average particle size 1.5 μm Conductive fine particles (C-9): Fukuda Metals Co., Ltd., spherical silver powder, average particle size 0.8 μm
[0072] <Other ingredients (D-1) to (D-6)> Other ingredients (D-1): Kao Corporation, non-ionic dispersant, Emulgen 102KG, solids 100% Other ingredients (D-2): Nippon Electric Glass Co., Ltd., glass powder, LS1401S, 100% solids Other ingredients (D-3): Asahi Kasei Chemicals Corporation, blocked isocyanate, Duranate SBN-70D, dipropylene glycol methyl ether solution with 70% solids Other ingredients (D-4): Titanate coupling agent, Plainact KR-TTS, manufactured by Ajinomoto Fine-Techno Co., Ltd., solids concentration 100% Other ingredients (D-5): Nippon Aerosil Co., Ltd., fumed silica, AEROSIL R202 Other ingredients (D-6): Shin-Nakamura Chemical Co., Ltd., liquid UV monomer, NK Ester TMPT, solids concentration 100%
[0073] <Example 1: Preparation of conductive resin composition for molded film (F-1)> 20.0 parts of resin (A-1) was dissolved in 30.0 parts of solvent (B-1), and 80.0 parts of conductive fine particles (C-1) were mixed and stirred, and the mixture was kneaded five times using a three-roll mill (Kodaira Seisakusho Co., Ltd.) to obtain a conductive resin composition for molded films (F-1). The recovery tan δ was 28 and the high shear viscosity was 400 (Pa s).
[0074] <Example 2: Preparation of conductive resin composition for molded film (F-2)> 20.0 parts of resin (A-2) was dissolved in 30.0 parts of solvent (B-1), 80.0 parts of conductive fine particles (C-1) were mixed and stirred, and the mixture was kneaded five times with a three-roll mill (Kodaira Seisakusho Co., Ltd.) to obtain a conductive resin composition for molded films (F-2). The recovery tan δ was 3.00 and the high shear viscosity was 40.0 (Pa s).
[0075] <Example 3: Preparation of conductive resin composition for molded film (F-3)> 20.0 parts of resin (A-3) was dissolved in 30.0 parts of solvent (B-1), 80.0 parts of conductive fine particles (C-1) were mixed and stirred, and the mixture was kneaded five times with a three-roll mill (Kodaira Seisakusho Co., Ltd.) to obtain a conductive resin composition for molded films (F-3). The recovery tan δ was 4.50 and the high shear viscosity was 60.0 (Pa s).
[0076] <Example 4: Preparation of conductive resin composition for molded film (F-4)> 20.0 parts of resin (A-4) was dissolved in 30.0 parts of solvent (B-1), 80.0 parts of conductive fine particles (C-1) were mixed and stirred, and the mixture was kneaded five times with a three-roll mill (Kodaira Seisakusho Co., Ltd.) to obtain a conductive resin composition for molded films (F-4). The recovery tan δ was 2.00 and the high shear viscosity was 15.0 (Pa s).
[0077] <Example 5: Preparation of conductive resin composition for molded film (F-5)> 20.0 parts of resin (A-5) was dissolved in 30.0 parts of solvent (B-1), 80.0 parts of conductive fine particles (C-1) were mixed and stirred, and the mixture was kneaded five times with a three-roll mill (Kodaira Seisakusho Co., Ltd.) to obtain a conductive resin composition for molded films (F-5). The recovery tan δ was 4.00 and the high shear viscosity was 50.0 (Pa s).
[0078] <Example 6: Preparation of conductive resin composition for molded film (F-6)> 20.0 parts of resin (A-1) was dissolved in 30.0 parts of solvent (B-1), 80.0 parts of conductive fine particles (C-2) were mixed and stirred, and the mixture was kneaded five times with a three-roll mill (Kodaira Seisakusho Co., Ltd.) to obtain a conductive resin composition for molded films (F-6). The recovery tan δ was 28.0 and the high shear viscosity was 400 (Pa s).
[0079] <Example 7: Preparation of conductive resin composition for molded film (F-7)> 20.0 parts of resin (A-1) was dissolved in 30.0 parts of solvent (B-1), 80.0 parts of conductive fine particles (C-3) were mixed and stirred, and the mixture was kneaded five times with a three-roll mill (Kodaira Seisakusho Co., Ltd.) to obtain a conductive resin composition for molded films (F-7). The recovery tan δ was 28.0 and the high shear viscosity was 400 (Pa s).
[0080] <Example 8: Preparation of conductive resin composition for molded film (F-8)> 20.0 parts of resin (A-1) was dissolved in 30.0 parts of solvent (B-1), 80.0 parts of conductive fine particles (C-4) were mixed and stirred, and the mixture was kneaded five times with a three-roll mill (Kodaira Seisakusho Co., Ltd.) to obtain a conductive resin composition for molded films (F-8). The recovery tan δ was 28.0 and the high shear viscosity was 400 (Pa s).
[0081] <Comparative Example 1: Preparation of conductive resin composition for molded film (F-9)> 20.0 parts of resin (A-1) was dissolved in 30.0 parts of solvent (B-1), 80.0 parts of conductive fine particles (C-1) were mixed and stirred, and the mixture was kneaded once using a three-roll mill (Kodaira Seisakusho Co., Ltd.) to obtain a conductive resin composition for molded films (F-9). The recovery tan δ was 40.0 and the high shear viscosity was 400 (Pa s).
[0082] <Comparative Example 2: Preparation of conductive resin composition for molded film (F-10)> 20.0 parts of resin (A-1) was dissolved in 30.0 parts of solvent (B-1), and 80.0 parts of conductive fine particles (C-1) were mixed and stirred for 10 minutes with a planetary mixer UFO1.5 manufactured by EME at 1300 rpm revolution and 1000 rpm rotation to obtain a conductive resin composition for molded films (F-10). The recovery tan δ was 40.0 and the high shear viscosity was 400 (Pa s).
[0083] <Comparative Example 3: Preparation of conductive resin composition for molded film (F-11)> 20.0 parts of resin (A-1) was dissolved in 30.0 parts of solvent (B-1), and 80.0 parts of conductive fine particles (C-1) were mixed and stirred, and then further mixed at 1000 rpm for 10 minutes using a high-speed disperser Homo Disper 2.5 type manufactured by PRIMIX Co., Ltd. to obtain a conductive resin composition for molded films (F-11). The recovery tan δ was 40.0 and the high shear viscosity was 400 (Pa s).
[0084] <Comparative Example 4: Preparation of conductive resin composition for molded film (F-12)> 4.0 parts of resin (A-6) was dissolved in 14.5 parts of solvent (B-1), and 80.0 parts of conductive fine particles (C-2), 1.5 parts of other components (D-1), and 2.0 parts of other components (D-2) were mixed and stirred, and the mixture was kneaded once using a three-roll mill (Kodaira Seisakusho Co., Ltd.) to obtain a conductive resin composition for molded films (F-12). The recovery tan δ was 0.40, and the high shear viscosity was 350 (Pa s).
[0085] <Comparative Example 5: Preparation of conductive resin composition for molded film (F-13)> 4.0 parts of resin (A-6) was dissolved in 14.5 parts of solvent (B-1), and 80.0 parts of conductive fine particles (C-2), 1.5 parts of other components (D-1), and 2.0 parts of other components (D-2) were mixed and stirred, and the mixture was kneaded five times with a three-roll mill (Kodaira Seisakusho Co., Ltd.) to obtain a conductive resin composition for molded films (F-13). The recovery tan δ was 0.45, and the high shear viscosity was 350 (Pa·s).
[0086] <Comparative Example 6: Preparation of conductive resin composition for molded film (F-14)> 15.0 parts of resin (A-7) was dissolved in 20.0 parts of solvent (B-2), 65.0 parts of conductive fine particles (C-5) were mixed and stirred, and the mixture was kneaded once using a three-roll mill (Kodaira Seisakusho Co., Ltd.) to obtain a conductive resin composition for molded films (F-14). The recovery tan δ was 0.30 and the high shear viscosity was 350 (Pa s).
[0087] <Comparative Example 7: Preparation of conductive resin composition for molded film (F-15)> 15.0 parts of resin (A-7) was dissolved in 20.0 parts of solvent (B-2), 65.0 parts of conductive fine particles (C-5) were mixed and stirred, and the mixture was kneaded five times with a three-roll mill (Kodaira Seisakusho Co., Ltd.) to obtain a conductive resin composition for molded films (F-15). The recovery tan δ was 0.40 and the high shear viscosity was 400 (Pa s).
[0088] <Comparative Example 8: Preparation of conductive resin composition for molded film (F-16)> 1.0 part of resin (A-8) was dissolved in 8.8 parts of solvent (B-1) and 5.7 parts of solvent (B-5), and 84.5 parts of conductive fine particles (C-6) were mixed and stirred, and the mixture was kneaded once using a three-roll mill (Kodaira Seisakusho Co., Ltd.) to obtain a conductive resin composition for molded films (F-16). The recovery tan δ was 0.45 and the high shear viscosity was 350 (Pa s).
[0089] <Comparative Example 9: Preparation of conductive resin composition for molded film (F-17)> 1.0 part of resin (A-8) was dissolved in 8.8 parts of solvent (B-1) and 5.7 parts of solvent (B-5), and 84.5 parts of conductive fine particles (C-6) were mixed and stirred, and the mixture was kneaded five times with a three-roll mill (Kodaira Seisakusho Co., Ltd.) to obtain a conductive resin composition for molded films (F-17). The recovery tan δ was 0.40 and the high shear viscosity was 400 (Pa·s).
[0090] <Comparative Example 10: Preparation of conductive resin composition for molded film (F-18)> 0.3 parts of resin (A-9) was dissolved in 1.9 parts of solvent (B-1) and 15.0 parts of solvent (B-3), and 77.8 parts of conductive fine particles (C-7) and 5.0 parts of other components (D-6) were mixed and stirred, and the mixture was kneaded once using a three-roll mill (Kodaira Seisakusho Co., Ltd.) to obtain a conductive resin composition for molded films (F-18). The recovery tan δ was 50.0 and the high shear viscosity was 500 (Pa·s).
[0091] <Comparative Example 11: Preparation of conductive resin composition for molded film (F-19)> 0.3 parts of resin (A-9) was dissolved in 1.9 parts of solvent (B-1) and 15.0 parts of solvent (B-3), and 77.8 parts of conductive fine particles (C-7) and 5.0 parts of other components (D-6) were mixed and stirred, and the mixture was kneaded five times using a three-roll mill (Kodaira Seisakusho Co., Ltd.) to obtain a conductive resin composition for molded films (F-19). The recovery tan δ was 60.0 and the high shear viscosity was 550 (Pa·s).
[0092] <Comparative Example 12: Preparation of conductive resin composition for molded film (F-20)> 4.2 parts of resin (A-10) and 1.7 parts of resin (A-11) were dissolved in 12.5 parts of solvent (B-1) and 0.7 parts of solvent (B-4), and 52.3 parts of conductive fine particles (C-8), 22.4 parts of conductive fine particles (C-9), 1.7 parts of other components (D-3), 0.8 parts of other components (D-4), and 4.0 parts of other components (D-5) were mixed and stirred, and the mixture was kneaded once using a three-roll mill (manufactured by Kodaira Seisakusho) to obtain a conductive resin composition (F-20) for molded films. The recovery tan δ was 35.0, and the high shear viscosity was 500 (Pa·s).
[0093] <Comparative Example 13: Preparation of conductive resin composition for molded film (F-21)> 4.2 parts of resin (A-10) and 1.7 parts of resin (A-11) were dissolved in 12.5 parts of solvent (B-1) and 0.7 parts of solvent (B-4), and 52.3 parts of conductive fine particles (C-8), 22.4 parts of conductive fine particles (C-9), 1.7 parts of other components (D-3), 0.8 parts of other components (D-4), and 4.0 parts of other components (D-5) were mixed and stirred, and the mixture was kneaded once using a three-roll mill (manufactured by Kodaira Seisakusho) to obtain a conductive resin composition (F-21) for molded films. The recovery tan δ was 40.0 and the high shear viscosity was 500 (Pa·s).
[0094] <Examples 9 to 16 and Comparative Examples 14 to 26> Conductive compositions for molded films (F-1) to (F-21) were each printed on a polycarbonate (PC) base film (Teijin, Panlite 2151, thickness 300 μm, 300 mm × 210 mm) using a screen printer (Minoscreen, Minomat SR5575 semi-automatic screen printer) at a printing speed of 100 mm. Then, by heating in a hot air drying oven at 120 ° C. for 30 minutes, a molded film with a conductive layer having a square solid pattern with a width of 15 mm, a length of 30 mm, and a thickness of 10 μm, a linear pattern with a line width of 3 mm, a length of 60 mm, and a thickness of 10 μm, and a stripe pattern with a line width of 150 μm, a line distance of 150 μm, and a length of 60 mm was obtained.
[0095] [(1) Volume resistivity measurement] The volume resistivity (Ω cm) of the 15 mm × 30 mm square solid conductive layers formed on the molded films of Examples 9 to 16 and Comparative Examples 14 to 26 was measured using a resistivity meter (Mitsubishi Chemical Analytech Co., Ltd., Loresta GP MCP-T610 resistivity meter, JIS-K7194 compliant, 4-terminal 4-probe constant current application method) (4-terminal probes spaced 0.5 cm apart). The results are shown in Table 3.
[0096] [(2) Wiring resistance evaluation] The formed films of Examples 9 to 16 and Comparative Examples 14 to 26 were cut into a length of 70 mm and a width of 10 mm so that the conductive layer of a linear pattern of 3 mm x 60 mm formed in the center was in the middle, and used as a measurement coupon. On the surface of the measurement coupon opposite the conductive layer, two lines perpendicular to the conductive layer from the longitudinal end were added with oil-based marker at 4 cm intervals as marks. The resistance values of positions 4 cm apart according to these marks were measured using a tester, and these were taken as wiring resistance (Ω). The results are shown in Table 3.
[0097] [(3) Hot stretching evaluation 1] The measurement coupons of Examples 9 to 16 and Comparative Examples 14 to 26 were stretched in the longitudinal direction at a stretching speed of 10 mm / min to an elongation rate of 125% in a heating oven at 160°C. After removing from the oven and cooling, the presence or absence of disconnection was evaluated using an optical microscope. In addition, the wiring resistance (Ω) was measured at positions corresponding to 4 cm intervals based on the original mark in the same manner as in the measurement of the wiring resistance described above, and the wiring resistance after stretching / wiring resistance before stretching was defined as the resistance variation rate (times) during thermal stretching, and each was evaluated according to the following criteria. The results are shown in Table 3. (Whether or not there is a break) A: No breaks were observed. B: 1 to 2 minor cracks were found C: Severe disconnection or peeling of the conductive coating was confirmed. (Resistance variation rate during hot stretching) A: 5 times or more but less than 10 times B: 10 times or more but less than 100 times C: 100 times or more
[0098] The elongation rate is a value calculated as follows. (Elongation rate) [%] = {(length after stretching - length before stretching) / (length before stretching)} x 100
[0099] [(4) Hot stretching evaluation 2] The heat stretching was evaluated according to the following criteria in the same manner as in the heat stretching evaluation 1, except that the elongation rate was changed to 150%. The results are shown in Table 3. (Whether or not there is a break) A: No breaks were observed. B: 1 to 2 minor cracks were found C: Severe disconnection or peeling of the conductive coating was confirmed. (Resistance variation rate during hot stretching) A: 10 times or more but less than 100 times B: 100 times or more but less than 1000 times C:1000 times or more
[0100] [(5) Evaluation of process resistance during manufacturing of molded products by overlay molding] A rectangular parallelepiped ABS resin molded product with a height of 10 mm and a length and width of 30 mm x 30 mm was placed so as to face the conductor side so as to overlap the position of the 3 mm x 60 mm linear pattern of the molded film of the above Examples 9 to 16 and Comparative Examples 14 to 26, and overlay molding was performed at a set temperature of 160 ° C. using a TOM molding machine (manufactured by Fuse Vacuum Co., Ltd.) to obtain a molded product in which the molded film molded into a rectangular parallelepiped shape and the ABS resin molded product are integrated. The scraping and resistance variation rate of the linear pattern wiring of this molded product were confirmed. The resistance variation rate was evaluated by measuring the wiring resistance (Ω) at a position corresponding to a 6 cm interval based on the original mark, and the wiring resistance after stretching / wiring resistance before stretching was defined as the resistance variation rate (times) during hot stretching, and each was evaluated according to the following criteria. The results are shown in Table 3. (Presence or absence of disconnection and resistance fluctuation rate) A: No wear on the wiring is observed, and the resistance fluctuation rate is between 10 times and 50 times. B: 1-2 chipped wire ends due to wear and tear, or resistance fluctuation rate is 50 times or more but less than 500 times C: One or more breaks in the wiring due to scraping were confirmed.
[0101] [(6) Evaluation of process resistance during manufacturing of molded products by film insert molding] A block-shaped metal mold having a rectangular protrusion in the center measuring 30 mm x 30 mm x 10 mm with a step of 10 mm was placed facing the opposite side of the conductor so as to overlap the position of the 3 mm x 60 mm linear pattern of the molded films of Examples 9 to 16 and Comparative Examples 14 to 26 above, and overlay molding was performed at a set temperature of 160°C using a TOM molding machine (manufactured by Fuse Vacuum Co., Ltd.) to obtain a moldable film molded into a rectangular parallelepiped shape and with a patterned conductor on the inside. Next, the molded film molded into the rectangular parallelepiped shape was set in an injection molding machine (IS170 (i5), manufactured by Toshiba Machine Co., Ltd.) equipped with a valve gate type in-mold molding test mold, and a molded body integrated with the molded film with a patterned conductor was obtained by injection molding PC / ABS resin (LUPOYPC / ABSHI5002, manufactured by LG Chem Co., Ltd.) (injection conditions: screw diameter 40 mm, cylinder temperature 260 ° C., mold temperature (fixed side, movable side) 60 ° C., injection pressure 160 MPa (80%), holding pressure 100 MPa, injection speed 60 mm / sec (28%), injection time 4 seconds, cooling time 20 seconds). Washout due to injection of molten resin of the linear pattern of this molded body (deformation or disconnection of the wiring pattern due to the temperature and injection pressure of the molten thermoplastic resin) and resistance variation rate were confirmed. The resistance variation rate was evaluated by measuring the wiring resistance (Ω) at positions corresponding to 6 cm intervals based on the original mark, and the wiring resistance after stretching / wiring resistance before stretching was defined as the resistance variation rate (times) during thermal stretching. The results are shown in Table 3. (Presence or absence of disconnection and resistance fluctuation rate) A: No washout of wiring is observed, and the resistance fluctuation rate is between 10 times and 50 times. B: Wiring distortion due to mild washout is confirmed, or resistance fluctuation rate is 50 times or more but less than 500 times. C: One or more breaks due to washout in the wiring are confirmed.
[0102] [Table 1]
[0103] [Table 2]
[0104] [Table 3]
[0105] [Summary of results] It became clear that in the conductive layers of Comparative Examples 14 to 26, in which the recovery tan δ does not satisfy the range of claim 1, breakage occurs or the resistance value increases when the molded film is stretched at high temperatures during the three-dimensional molding process, especially when the stretching elongation is large.
[0106] On the other hand, from the results of Examples 9 to 16, the conductive composition of this embodiment does not break even when the stretching elongation is large when stretched at high temperatures during the three-dimensional molding process of the molded film, and the increase in resistance value is also well suppressed. This is thought to be because the recovery tan δ of the conductive composition of this embodiment satisfies 0.5 to 30, and moderate aggregation occurs between the conductive fine particles in the composition, and the conductive path in the conductive layer after final curing is firmly formed, so that the path does not collapse even during stretching, and the conductivity is maintained even after stretching. The present inventors think that a conductive resin composition with high network properties forms a conductive path that is resistant to stretching. When the dispersion ability of the combination of the resin and the conductive fine particles is high, the network property is improved by finely dispersing the particles under appropriate kneading conditions. On the other hand, when the dispersion ability of the combination of the resin and the conductive fine particles is low, large aggregation is formed due to overdispersion of the particles under inappropriate kneading conditions, and good network property cannot be obtained. From the above, in order to achieve high network properties in this embodiment, that is, to satisfy the predetermined recovery tan δ range, it is essential to knead the material under appropriate dispersion conditions suited to the material used. The above-mentioned effects were even more excellent when the viscosity at a shear rate of 100 (1 / s) satisfied the relationship of 3.00 (Pa s) or more and 300 (Pa s) or less, and were still more excellent when the resin (A) had at least one reactive functional group of a hydroxyl group or a carboxyl group, had a glass transition point of 10°C or more and 110°C or less, and had a weight average molecular weight of 10,000 or more and 100,000 or less.
[0107] Furthermore, due to the above-mentioned characteristics, a molded film having a conductive layer of the conductive composition of the present invention has been able to obtain an excellent wiring-integrated molded body even when the substrate surface has an uneven three-dimensional shape, particularly a complex three-dimensional shape having steep steps.
[0108] Thus, the molded film and wiring-integrated molded body using the conductive composition of this embodiment can be directly applied to plastic housings and three-dimensional parts for home appliances, automobile parts, robots, drones, etc., to make it possible to directly fabricate lightweight and space-saving circuits, touch sensors, antennas, heating elements (heaters), electromagnetic shields, inductors (coils), resistors, and mount various electronic components without compromising design freedom. Also, it is extremely useful for making electronic devices lighter, thinner, shorter, and smaller, improving design freedom, and making them more multifunctional. [Explanation of symbols]
[0109] 1 Base film 2 Conductive layer 3 Decorative layer 4. Electronic Components 5-pin 10 Forming film 11 Mold 12 Injection mold 13 Opening 14 Injection 15 Increase 16 Pressurization 17 Resin 20 Base material 21 Upper chamber box 22 Lower chamber box 30 Molded body
Claims
1. A conductive composition for producing a molded film for forming a conductive circuit on a substrate surface having an uneven surface or a three-dimensional curved surface, comprising: a coating composition comprising a resin (A), a solvent (B) and conductive fine particles (C), which is subjected to a step of applying a shear (rotation in one direction) speed of 1000 ( / s) at 25° C. for 60 seconds, and then a step of measuring the storage modulus for 200 seconds while applying a strain of 1% at a frequency of 1 Hz; the storage modulus at the end of the measurement (200 seconds after the start of the measurement) is taken as 100%, and when the storage modulus reaches a value of 90%, the tan δ is 0.50 or more and 30 or less; Resin (A) contains at least one selected from the group consisting of acrylic resins, vinyl ether resins, polyether resins, polyester resins, polyurethane resins, epoxy resins, phenoxy resins, polycarbonate resins, polyvinyl chloride resins, polyolefin resins, styrene block copolymer resins, polyamide resins, and polyimide resins; The solvent (B) contains a solvent having a boiling point of 180° C. or more and 270° C. or less, The conductive fine particles (C) include at least one selected from the group consisting of metal fine particles, carbon fine particles, and conductive oxide fine particles; The average particle size of the conductive fine particles (C) is 0.2 μm or more and less than 30 μm; Conductive compositions for formed films.
2. 2. The conductive composition for molded films according to claim 1, which has a viscosity at 25° C. and a shear rate of 100 (1 / s) of 3.00 (Pa·s) or more and 300 (Pa·s) or less.
3. 3. The conductive composition for molded films according to claim 1 or 2, wherein the resin (A) has at least one reactive functional group selected from the group consisting of a hydroxyl group and a carboxyl group, has a glass transition point of 10°C or higher and 110°C or lower, and has a weight average molecular weight of 10,000 or higher and 100,000 or lower.
4. The conductive composition for molded films according to any one of claims 1 to 3, wherein the conductive fine particles (C) have an average particle size of 0.5 μm or more and less than 30 μm, and include at least one selected from the group consisting of silver powder, copper powder, silver-coated powder, copper alloy powder, and carbon fine particles.
5. The conductive composition for formed films according to claim 4 , wherein the conductive fine particles (C) comprise a flake-shaped conductive powder having an average particle size of 2 μm or more and less than 15 μm.
6. A molded film for forming a conductive circuit on a substrate surface having an uneven surface or a three-dimensional curved surface, A molded film comprising a base film and a conductive layer formed from the conductive composition for molded films according to any one of claims 1 to 5 on the base film.
7. A step of placing the formed film according to claim 6 on a substrate; and a step of integrating the molded film and the substrate by an overlay molding method.
8. forming the formed film according to claim 6 into a predetermined shape; placing the formed film in an injection mold; A method for producing a molded article, comprising the steps of: molding a substrate by injection molding; and integrating the molded film with the substrate.
9. placing the molded film according to claim 6 in an injection mold; A method for producing a molded article, comprising the steps of: molding a substrate by injection molding; and transferring a conductive layer in the molded film to the substrate.
Citation Information
Patent Citations
Conductive paste and laminated ceramic electronic part
JP2003124052A
Decorative sheet and manufacturing process for the same
JP2007296848A
Paste for forming thick film
JP2010018675A
Electroconductive ink, and laminate with electroconductive pattern and method for producing the same
JP2011252140A
Conductive circuit integrated molded product and method of manufacturing the same
JP2012011691A